Searching for Bioethical Prescriptions in a Moral Lab - Soniewicka, Marta (ETHICS IN PROGRESS, 2015)
The paper reviews the book written by F.M. Kamm, entitled Bioethical Prescriptions: To Create, End, Choose, and Improve Lives (published in Oxford: Oxford University Press in 2013, pp. 599). Kamm is one of the most prominent analytical philosophers in moral philosophy, known from such works as Intricate Ethics (2007). She defends the rights-based approach to ethics and is also famous from constructing multilayered moral dilemmas. The review poses methodological questions, of whether scientific-like thought experiments performed in a moral lab, and the Method of Hypothetical Cases are able to transform our ethical dilemmas and provide any solutions. In the final part of the review, the first chapter of the book on Tolstoy’s essay (The Death of Ivan Ilych) is discussed in more detail.